2011
DOI: 10.1186/1472-6963-11-261
|View full text |Cite
|
Sign up to set email alerts
|

The effect of internal marketing on job satisfaction in health services: a pilot study in public hospitals in Northern Greece

Abstract: BackgroundThe purpose of this study was to explore the effect of internal marketing on job satisfaction in health services, particularly in public hospitals in Northern Greece.MethodsA questionnaire with three sections was used. The first one referred to internal marketing by using Foreman and Money's scale, while the second one contained questions on job satisfaction based on Stamps and Piermonte's work. The last section included demographic questions. Three categories of health care professionals, nurses, do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 35 publications
3
26
0
5
Order By: Relevance
“…However, there are very few studies that have rigorously evaluated the impact of such HRH interventions on the job satisfaction of health professionals (8183), and none from lower income countries. In the absence of such evidence, our results caution against simplistic assumptions about the effectiveness of these interventions.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are very few studies that have rigorously evaluated the impact of such HRH interventions on the job satisfaction of health professionals (8183), and none from lower income countries. In the absence of such evidence, our results caution against simplistic assumptions about the effectiveness of these interventions.…”
Section: Discussionmentioning
confidence: 99%
“…The results of the analysis support the findings of the studies in the literature. The studies in the hotel sector (Hwang andChi, 2005 andGounaris, 2008), hospitals and medical centers (Chang and Chang, 2007;Iliopoulos and Priporas, 2011;Ahmad and Al-Borie ,2012;Pantouvakis, 2012;Dahl and Peltier, 2014and Chen et al 2015, Atlay Işık and Altunoğlu,2016b, education sector (Demir et al 2008;Usta, 2009;Başaran et al 2011);Ting, 2011;Hung, 2012;Ogunnaike et al 2012; Omar Salem, Kameswari and Rajyalakshmi, 2012;Barzoki and Ghujali, 2013;and De Bruin-Reynolds et al 2015) and sport schools and centers (Yıldız, 2011 andChiu et al 2014) have found similar results related to internal marketing activities and job satisfaction of employees.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Além disso, existe uma correlação positiva entre satisfação no trabalho e satisfação do cliente. Se a força de trabalho está comprometida e alinhada com a missão da empesa, ela será um recurso valioso e estratégico para dirigir o desempenho organizacional (ILIOPOULOS;PRIPORAS, 2011;VASCONCELOS FILHO et al, 2016).…”
Section: Satisfação No Trabalhounclassified